Evaluating the Role of Galectin-1, Adiponectin, Leptin, and Adiponectin/Leptin Ratio as Risk Factors for Cardiovascular Diseases - Arkawazi, Lizan; Abdulateef, Darya; Mahmood, Trifa (Hormone and Metabolic Research)
Cardiovascular diseases (CVDs) are a leading cause of death globally. Early identification of individuals at elevated risk is essential for improving preventive measures and patient outcomes. Biomarkers like Galectin-1, leptin, and adiponectin are known to play roles in metabolic processes, with a low adiponectin/leptin ratio indicating a heightened cardiometabolic risk. However, the association between Galectin-1, leptin, adiponectin, and the adiponectin/leptin ratio with CVD risk scores is not well understood. This study aims to assess these markers’ correlation with CVD risk and their potential utility as predictors. This cross-sectional study assessed 135 healthy adults through questionnaires and blood pressure measurements. Each participant's cardiovascular (CV) risk was estimated, with serum Galectin-1, adiponectin, and leptin levels measured. Comparisons of adipokines levels between age-groups were conducted. The associations between variables were assessed, and linear regression was applied with cardiovascular risk score as the outcome. Statistical significance was set at p < 0.05. After excluding fifteen individuals, 122 subjects (62 males, 60 females; mean age 43.8 years) were included in the study. Leptin levels correlated positively with CV risk score and LDL levels in younger individuals, while the adiponectin/leptin ratio showed a negative correlation with LDL and CV risk scores across age groups. Smoking was a strong predictor of CV risk in younger participants, whereas diabetes, cholesterol/HDL ratio, and leptin were significant predictors in the middle-aged group (p < 0.05). Among measured adipokines, leptin is as a key predictor of cardiovascular risk, alongside established factors like smoking, diabetes, and cholesterol/HDL ratio.